Recurrent respiratory tract infections in children might be associated with vitamin A status: a case-control study - Zhang, Xuguang; Dai, Xuezheng; Li, Xianan; Xie, Xun; Chen, Yiru; Chen, Yanping; Guan, Haoyang; Zhao, Yan (Frontiers in Pediatrics, 2024)
Background: Recurrent respiratory tract infections (RRTIs) are common in children and its development might be associated with vitamin A deficiency according to recent research. The aim of this study was to understand the relation between vitamin A status and RRTIs in children, and the relation between dietary intake of vitamin A and RRTIs. Methods: 2,592 children aged 0.5-14 years from Heilongjiang province of China participated in the survey. The RRTI group consisted of 1,039 children with RRTIs, while 1553 healthy children were included in the control group. The levels of serum vitamin A were determined by high performance liquid chromatography (HPLC); dietary information was collected with the Food Frequency Questionnaire (FFQ).Results: Serum vitamin A concentration in the RRTI group was significantly lower than that in the control group (0.27±0.09 mg/L vs. 0.29±0.09 mg/L) (P<0.01). The odds ratios (ORs) for vitamin A insufficiency and deficiency were 1.55 (95% CI: 1.30-1.84) and 2.30 (95% CI: 1.182-2.90) respectively, current respiratory tract infection (RTI) symptoms, whereas 1.33 (95% CI:1.05-1.69) and 4.74 (95% CI:3.19-7.03) with the occurrence of RRTIs respectively. Analysis of dietary intake of vitamin A-rich foods showed that the sufficient intakes of milk and eggs reduced the risk of RRTIs [OR: 0.58 (95% CI:0.47-0.73), 0.37(95% CI:0.26-0.53), respectively]. Even an insufficient intake of animal liver was associated with lower RRTIs [OR: 0.45(95% CI:0.38-0.53)], while only an excessive intake of meat had the same effect [OR: 0.85 (95% CI:0.68-1.06)]. Conclusions: Low serum vitamin A concentration was associated with high incidence of RRTIs in children in northeast China; low serum vitamin A concentrations and the current RTI symptoms were associated with the development of RRTIs; and low intakes of vitamin A-rich foods were also associated with the development of RRTIs.